2016
DOI: 10.1038/srep33280
|View full text |Cite
|
Sign up to set email alerts
|

A polymorphic (GA/CT)n- SSR influences promoter activity of Tryptophan decarboxylase gene in Catharanthus roseus L. Don

Abstract: Simple Sequence Repeats (SSRs) of polypurine-polypyrimidine type motifs occur very frequently in the 5′ flanks of genes in plants and have recently been implicated to have a role in regulation of gene expression. In this study, 2 accessions of Catharanthus roseus having (CT)8 and (CT)21 varying motifs in the 5′UTR of Tryptophan decarboxylase (Tdc) gene, were investigated for its role in regulation of gene expression. Extensive Tdc gene expression analysis in the 2 accessions was carried out both at the level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 65 publications
2
29
0
Order By: Relevance
“…The mutation length of the 5 ′ UTR Py-rich stretch motif influences promoter activity of the tryptophan decarboxylase (tdc) gene in Catharanthus roseus. 36 In our present study, the 5 ′ UTR Py-rich stretch motif mainly existed in the L-5UPS form in the R biotypes with high EPSPS expression, whereas the 5 ′ UTR Py-rich stretch motif mainly existed in the S-5UPS form in the S biotype with low EPSPS expression after glyphosate treatment (Fig. 4).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The mutation length of the 5 ′ UTR Py-rich stretch motif influences promoter activity of the tryptophan decarboxylase (tdc) gene in Catharanthus roseus. 36 In our present study, the 5 ′ UTR Py-rich stretch motif mainly existed in the L-5UPS form in the R biotypes with high EPSPS expression, whereas the 5 ′ UTR Py-rich stretch motif mainly existed in the S-5UPS form in the S biotype with low EPSPS expression after glyphosate treatment (Fig. 4).…”
Section: Discussionsupporting
confidence: 51%
“…Studies on the promoter function of the amorpha‐4,11‐diene synthase (ADS) gene in Artemisia annua and the high‐molecular‐weight glutenin subunit (HMW‐GS) gene in Triticum aestivum demonstrated that the 5′ UTR Py‐rich stretch elements were important factors in the enhancement of the expression of the ADS and HMW‐GS genes. The mutation length of the 5′ UTR Py‐rich stretch motif influences promoter activity of the tryptophan decarboxylase ( tdc ) gene in Catharanthus roseus . In our present study, the 5′ UTR Py‐rich stretch motif mainly existed in the L‐5UPS form in the R biotypes with high EPSPS expression, whereas the 5′ UTR Py‐rich stretch motif mainly existed in the S‐5UPS form in the S biotype with low EPSPS expression after glyphosate treatment (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Before infiltration, effector, reporter, and internal control solutions were combined at a 1:1:1 ratio and mixed well. Infiltration of N. benthamiana leaves was performed as previously described (Kumar and Bhatia, 2016). Two days after infiltration, leaf discs were collected, frozen in liquid nitrogen, and ground to powder for protein extraction.…”
Section: Plasmid Construction and Nicotiana Benthamiana Leaf Infiltramentioning
confidence: 99%
“…All the above effects caused by SSR variations in genes can lead to phenotypic changes in organisms (Li et al, 2004). For example, (CT) n -SSRs located in the 5 -UTR of tryptophan decarboxylase will influence the promoter activity and thus significantly enhances the level of gene expression in plants (Kumar and Bhatia, 2016). In Myzus persicae, the expansion of a di-nucleotide microsatellite in the promoter region of a P450 gene lead to its overexpression, and this process enhanced the resistance to neonicotinoid insecticides in this aphid (Bass et al, 2013).…”
Section: Discussionmentioning
confidence: 99%